THE FORMATION OF THE VOLITIONAL ACTIVITY OF STUDENTS OF EDUCATIONAL INSTITUTIONS OF THE MIA OF RUSSIA IN THE PROCESS OF PHYSICAL EDUCATION - Boris Anisimov; Elena Kozenko; Tatiana Prokopenko (Вестник Северо-Кавказского федерального университета)
This article discusses some aspects of the formation of strong-willed activity of cadets of educational institutions of the MIA of Russia in the process ofphysical education. The notion of will as well as its primary purpose and psychological feature.